2017
DOI: 10.1210/js.2017-00277
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Change in the Ligand-Binding Pocket via a KISS1R Mutation (P147L) Leads to Isolated Gonadotropin-Releasing Hormone Deficiency

Abstract: Context:Kisspeptin receptor (KISS1R) is expressed in hypothalamic gonadotropin-releasing hormone neurons and responsible for pubertal onset and reproductive functions. KISS1R mutations remain a rare cause of congenital hypogonadotropic hypogonadism (CHH).Objective:The aim of this study was to identify the genetic cause of CHH in a patient and to functionally characterize a KISS1R mutation.Design:The patient was a 47-year-old Japanese man whose parents were first cousins. He lacked secondary sexual characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…This could explain the sudden increase in the RMSD plot of FRα in the FA–FRα system at 65 ns ( Figure 7 a). Expansion in the binding pocket may also be an indication of the loss of ligand interactions where the ligand exited from the pocket [ 71 ], as observed in PTX after 80 ns of the MD simulation. It is also observed that after 65 ns, the volumes of binding sites for FOL03–FRα and FOL08–FRα were smaller than for the FA–FRα system.…”
Section: Resultsmentioning
confidence: 99%
“…This could explain the sudden increase in the RMSD plot of FRα in the FA–FRα system at 65 ns ( Figure 7 a). Expansion in the binding pocket may also be an indication of the loss of ligand interactions where the ligand exited from the pocket [ 71 ], as observed in PTX after 80 ns of the MD simulation. It is also observed that after 65 ns, the volumes of binding sites for FOL03–FRα and FOL08–FRα were smaller than for the FA–FRα system.…”
Section: Resultsmentioning
confidence: 99%
“…The minor allele frequency of the p.P147L (c.C440T) variant in KISS1R , as reported by the Tohoku Medical Megabank Organization (ToMMo), was 0.0005. Moreover, the P147L- KISS1R mutation reportedly causes an almost complete loss of function due to loss of ligand-binding affinity ( 9 ). Based on the 2015 American College of Medical Genetics and Genomics and the Association of Molecular Pathology (ACMG-AMP) guidelines ( 10 ), the P147L- KISS1R mutation was likely pathogenic.…”
Section: Case Presentationmentioning
confidence: 99%